Total protein, Mg and Ca determination and partial microbial characterization of fermented Cassava flour. - Villafuerte, Mary Kris Villavert
Fermentation of cassava is a traditional processing technique employed by cassava consuming populations to render the roots storable and palatable and to reduce its hydrogen cyanide (HCN) levels to acceptable amounts, but this process has a detrimental effect on its the protein, mineral and vitamin content. However, recent studies showed that fermentation of unpeeled cassava increases its protein content. This low-cost and easy means of increasing the protein content of cassava can be the solution to the prevalence of protein energy malnutrition (PEM) in countries where cassava is consumed as a staple., The protein content of cassava flour fermented unpeeled was determined through Bradford assay. For total calcium and magnesium determination, wet digestion method was done and mineral determination was conducted through atomic absorption spectrophotometric analysis. In vitro mineral analysis for calcium and magnesium was done to provide an estimate of the bioavailability of calcium and magnesium. Microbial analysis was done to charcterize the microorganisms present in the fermentation solution which may have contributed to the protein increase of the roots. Results showed that there was a significant increase in the protein content of fermented cassava flour fermentation as prolonged. The increase in protein was 17.52 percent for the sample fermented fort three days (FU3) and 31.85 percent for the sample fermented for six days (FU6). T-test revealed significant decrease in calcium and magnesium content of the fermented samples with prolonged fermentation. The decease in the calcium content was 20.94 percent for FU3 and 48.28 percent for FU6 while the decrease in magnesium content was 10.74 percent and 10.25 percent for FU3 and FU6, respectively. Pearson correlationt est revealed an inversely proportional relationship between total protein and total calcium content such that the calcium content decreases as the protein content increases. In vitro mineral availability showed that bioavailability of calcium was highest at the 9th hour of dialysis while that of magnesium at the 3rd hour of dialysis. Microbial analysis revealed an abundance of rod shaped and Gram positive bacteria in the fermentation solution. It was observed that this bacteria continue to drive in the fermentation solution despite of the drop in pH (6.93-5.12) as the fermentation was prolonged (0-5 days). Results from the microbial analysis however, were not sufficient to establish a correlation on the increase in protein cassava and whether or not the microorganism isolated from the fermentation solution were responsible for it.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Flour, Cassava